2023
DOI: 10.1371/journal.pone.0276027
|View full text |Cite
|
Sign up to set email alerts
|

Physician burnout and symptom of anxiety and depression: Burnout in Consultant Doctors in Ireland Study (BICDIS)

Abstract: Background Burnout is a work related syndrome comprising three major dimensions: emotional exhaustion, depersonalisation and reduced professional efficacy. It is recognised that burnout may be associated with psychopathological sequelae, such as symptoms of anxiety and depression. Aims This study aimed to examine the relationship between burnout and symptoms of depression and anxiety in senior doctors in Ireland. We examined personality traits as a mediating factor on burnout, in relation to work related str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This close association between adverse mental health and burnout has been reported in other studies examining depression and anxiety. 18 As this study was cross-sectional, a cause–effect relationship cannot be determined. The finding of higher patient-related burnout (typically the last type to increase) in those with unchanged as opposed to deteriorated physical health, might at first glance seem surprising.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This close association between adverse mental health and burnout has been reported in other studies examining depression and anxiety. 18 As this study was cross-sectional, a cause–effect relationship cannot be determined. The finding of higher patient-related burnout (typically the last type to increase) in those with unchanged as opposed to deteriorated physical health, might at first glance seem surprising.…”
Section: Discussionmentioning
confidence: 96%
“…The association between intention to change job and burnout is well established. 15 , 18 This relationship is reciprocal, and it has been speculated that it may be mediated by organisational factors such as ineffective policies, inadequate workforce planning and recruitment, incompetent implementation planning and ineffective leadership. 18 Similarly, spending time outside of one's area of responsibilities can generate anxiety as well as a sense of inadequacy or lack of competence, and may be compensated for by increasing additional hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed a prevalence of 42%, and demonstrated that burnout was associated with lack of exercise and face-to-face contact with patients, despite the physicians having good salaries and a relatively low workload ( 19 ). In a secondary analysis, Crudden et al ( 20 ) found that approximately 26 and 14% of the study sample scored positively for depression and anxiety, respectively. They also showed that these symptoms were associated with high emotional exhaustion, reduced professional effectiveness, and increased work burden ( p < 0.001) ( 20 ).…”
Section: Epidemiology Of Mental Disorders Suicidal Ideation and Suici...mentioning
confidence: 99%
“…In a secondary analysis, Crudden et al ( 20 ) found that approximately 26 and 14% of the study sample scored positively for depression and anxiety, respectively. They also showed that these symptoms were associated with high emotional exhaustion, reduced professional effectiveness, and increased work burden ( p < 0.001) ( 20 ).…”
Section: Epidemiology Of Mental Disorders Suicidal Ideation and Suici...mentioning
confidence: 99%